Expedient stereoselective synthesis of trifluoromethylated pyranonaphthoquinones - Tuyet Anh, Dang Thi; Phuong, Hoang Thi; Doan, Vu Ngoc; Chinh, Pham The; Ha, Nguyen Thanh; Thu Ha, Nguyen Thi; Huy, Nguyen Hung; Anh, Ngo Quoc; Tuyen, Nguyen Van (Vietnam Journal of Chemistry, 2015)
Stereodefined and biologically relevant CF3-containing hydroxypyranonaphthoquinone carboxylates were prepared for the first time by a one-pot four-component condensation between 2-hydroxy-1,4-naphthoquinone, an aldehyde, ethyl 4,4,4-trifluoroacetoacetate and ammonium acetate. This transformation is presumed to proceed via aldol condensation/Mannich reaction followed by Michael addition and regio- and stereoselective 6-exo-trig cyclization, deamination and addition of water. Keywords. Hydroxypyranonaphthoquinone, ammonium acetate.